Peran Strategis Pesantren Dalam Meningkatkan Kualitas Pendidikan Islam Di Indonesia - Ayu Wardani; Andi Muhammad Anshar Amin; Idrus L. (Prodi PGSD Unsultra, 2026)
Islamic boarding schools (pesantren) are the oldest Islamic educational institutions in Indonesia, contributing significantly to character building, the development of Islamic knowledge, and improving the quality of national education. This study aims to analyze the strategic role of Islamic boarding schools in improving the quality of Islamic education in Indonesia through a literature study approach. The research method used is a literature review, compiling various scientific sources in the form of journals, books, articles, and policy documents relevant to Islamic boarding school education. Data analysis was conducted through data reduction techniques, theme classification, interpretation, and descriptive-analytical conclusion drawing. The study results indicate that Islamic boarding schools have a strategic role in five main aspects. First, Islamic boarding schools play a role in the formation of students' character and morals through education based on Islamic values. Second, Islamic boarding schools contribute to the integration of religious and general knowledge through the development of an adaptive curriculum. Third, Islamic boarding schools serve as centers for strengthening religious moderation and social tolerance in a multicultural society. Fourth, Islamic boarding schools play a role in human resource development by improving the quality of teaching staff and the skills of students. Fifth, Islamic boarding schools support the transformation of Islamic education through the use of technology and partnerships with various educational institutions. Thus, Islamic boarding schools not only function as traditional educational institutions, but also as agents of social change that are able to answer the challenges of Islamic education in the modern era.